Engineering statistics - Montgomery, Douglas C. (John Wiley, 2001)
Gives a treatment of engineering statistics, focusing on how statistics is integrated into the engineering problem-solving process. This work covers all major aspects of engineering statistics, including descriptive statistics, statistical test and confidence intervals for one and two samples, building regression models, and more.